Are naïve T cells and class-switched memory (IgD− CD27+) B cells not essential for establishment and maintenance of pregnancy? Insights from a case of common variable immunodeficiency with pregnancy. (December 2018) - Shigeta, Naoya; Nakamura, Hitomi; Kumasawa, Keiichi; Imai, Kohsuke; Saito, Shigeru; Sakaguchi, Shimon; Kimura, Tadashi
Abstract: The disruption of adaptive immune response has adverse effects on the establishment and maintenance of pregnancy. The adaptive immune system is regulated by several types of immune cells. However, there is limited information about cell hierarchy in the adaptive immune response to the establishment and maintenance of pregnancy in women. The assessment of the outcome of pregnancy in primary immunodeficiency diseases could help in understanding the cell hierarchy in the adaptive immune system during pregnancy. Common variable immunodeficiency (CVID) is a heterogeneous adaptive immune system disorder characterized by primary hypogammaglobulinemia. A few studies have previously reported the assessment of the T and B cell subpopulations in CVID patients. However, an assessment of the subpopulations of T and B cells and the outcome of pregnancy in women with CVID has not been reported till date. Most CVID patients show a general decrease in the expression of CD27 in B cells. The assessment of pregnancy and the subpopulations of T and B cells in CVID women with severe reduction in the naïve T and switched B cells could help understand whether these cells are essential for the establishment and maintenance of pregnancy in women.